Trained Immunity in Primary Sjögren’s Syndrome: Linking Type I Interferons to a Pro-Atherogenic Phenotype - Huijser, Erika; van Helden-Meeuwsen, Cornelia G.; Grashof, Dwin G. B.; Tarn, Jessica R.; Brkic, Zana; Huisman, Josje M. A.; Wahadat, M. Javad; van de Werken, Harmen J. G.; Lopes, Ana P.; van Roon, Joel A. G.; van Daele, Paul L. A.; Kamphuis, Sylvia; et al. (Frontiers in Immunology, 2022)
Background: Trained immunity – or innate immune memory – can be described as the long-term reprogramming of innate immune cells towards a hyperresponsive state which involves intracellular metabolic changes. Trained immunity has been linked to atherosclerosis. A subgroup of patients with primary Sjögren’s syndrome (pSS) exhibits systemic type I interferon (IFN) pathway activation, indicating innate immune hyperactivation. Here, we studied the link between type I IFNs and trained immunity in an in vitro monocytic cell model and peripheral blood mononuclear cells (PBMCs) from pSS patients. Methods: The training stimuli heat killed Candida albicans, muramyl dipeptide, IFNβ, and patient serum were added to THP-1 cells for 24 hours, after which the cells were washed, rested for 48 hours and subsequently re-stimulated with LPS, Pam3Cys, poly I:C, IFNβ or oxLDL for 4-24 hours. PBMCs from pSS patients and healthy controls were stimulated with LPS, Pam3Cys, poly I:C or IFNβ for 0.5-24 hours. Results: Training with IFNβ induced elevated production of pro-atherogenic cytokines IL-6, TNFα and CCL2, differential cholesterol- and glycolysis-related gene expression, and increased glucose consumption and oxLDL uptake upon re-stimulation. Type I IFN production was increased in Candida albicans- and IFNβ-trained cells after LPS re-stimulation, but was reduced after poly I:C re-stimulation. Training with muramyl dipeptide and IFNβ, but not Candida albicans, affected the IFN-stimulated gene expression response to IFNβ re-stimulation. PBMCs from pSS patients consumed more glucose compared with healthy control PBMCs and tended to produce more TNFα and type I IFNs upon LPS stimulation, but less type I IFNs upon poly I:C stimulation. Conclusions: Type I IFN is a trainer inducing a pro-atherogenic trained immunity phenotype in monocytes. Conversely, trained immunity also affects the production of type I IFNs and transcriptional response to type I IFN receptor re-stimulation. The phenotype of pSS PBMCs is consistent with trained immunity. This connection between type I IFN, trained immunity and cholesterol metabolism may have important implications for pSS and the pathogenesis of (subclinical) atherosclerosis in these patients.